2021
DOI: 10.1111/bjh.17419
|View full text |Cite
|
Sign up to set email alerts
|

Mantle cell lymphoma – advances in molecular biology, prognostication and treatment approaches

Abstract: Mantle cell lymphoma (MCL) is clinically characterised by its heterogenous behaviour with courses ranging from indolent cases that do not require therapy for years to highly aggressive MCL with a very limited prognosis. A better understanding of the complex biology of MCL has already led to the approval of several innovative agents, expanding the landscape of MCL therapies and improving therapeutic options especially for refractory/relapsed (R/R) disease.Nevertheless, to further optimise MCL treatment, early i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 111 publications
(175 reference statements)
0
42
2
1
Order By: Relevance
“…MCL often occurs in male patients in the Asian population, and the median age at initial presentation is 60 years, which is signi cantly lower than that in Western and American countries. In pathological subtypes, compared with previous reports, 10-15% of patients present with a more indolent subtype, non-nodular mantle cell lymphoma only accounted for 3.3% in our corhort and the majority of these patients have symptoms and treatment indications (19). Most newly diagnosed patients display aggressive disease features, blastic/pleomorphic mantle cell lymphoma accounted for 12.8%, ki-67 ≥ 30% was 57.7% and ki-67 ≥ 50% was 26.1%.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…MCL often occurs in male patients in the Asian population, and the median age at initial presentation is 60 years, which is signi cantly lower than that in Western and American countries. In pathological subtypes, compared with previous reports, 10-15% of patients present with a more indolent subtype, non-nodular mantle cell lymphoma only accounted for 3.3% in our corhort and the majority of these patients have symptoms and treatment indications (19). Most newly diagnosed patients display aggressive disease features, blastic/pleomorphic mantle cell lymphoma accounted for 12.8%, ki-67 ≥ 30% was 57.7% and ki-67 ≥ 50% was 26.1%.…”
Section: Discussioncontrasting
confidence: 54%
“…The standard frontline therapy for MCL is not completely uni ed, however, there is a general consensus that cytarabine-containing chemotherapy combined with autologous hematopoietic stem cell transplantation as the rst-line treatment for young and t patients, whereas older or un t patients are treated with combination chemo-immunotherapy according to different tolerance (9,(20)(21)(22)(23). Although the bene t of high-dose cytarabine is clear, due to different clinical trial results, the recognized uni ed regimen is not de nite.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate patient stratification, the usage of aggressive ICT regimens in young patients and rituximab maintenance together with new agents at relapse contributed to improved survival rates. Nevertheless, the long-term prognosis is still poor [ 76 ].…”
Section: Mantle Cell Lymphoma (Mcl)mentioning
confidence: 99%
“…Although the majority of MCL patients pursue an aggressive clinical course requiring immediate treatment, several investigators identified indolent forms of disease representing 10–15% of cases [ 34 ]. As mentioned above, these include not only the leukemic/non-nodal, SOX11-negative form but also rare, asymptomatic, nodal/extra-nodal forms with a low tumor burden, classical morphology on histopathology, low proliferation rate and an intact TP53 [ 51 , 76 ]. It was shown that these subsets may remain stable for years and that early treatment does not impact overall survival [ 77 , 78 ].…”
Section: Mantle Cell Lymphoma (Mcl)mentioning
confidence: 99%
See 1 more Smart Citation